2000
DOI: 10.1016/s0002-9440(10)64787-6
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Alterations in Interleukin-6/Soluble Interleukin-6 Receptor α Double-Transgenic Mice

Abstract: Interleukin-6 (IL-6), a major cytokine with diverse effects on cells mainly of the immune and hematopoietic systems, has been linked to several neurological disorders such as acquired immune deficiency syndrome dementia, multiple sclerosis, and Alzheimer's disease. Central nervous system (CNS)-specific expression of IL-6 caused neurodegeneration, massive gliosis, and vascular proliferation in transgenic mice. However, the effects of systemically circulating IL-6 and its receptor IL-6Ralpha on the CNS are unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 67 publications
(83 reference statements)
2
28
0
Order By: Relevance
“…We showed previously that overexpression of IL-6 in transgenic mice leads to a severe reactive gliosis (Brunello et al, 2000), and others demonstrated that the absence of IL-6 impairs reactive astroglial transformation (Klein et al, 1997). However, this effect appears to be dependent on the type of lesion, as MPTP-induced astrogliosis is not impaired in mice lacking IL-6 (Cardenas and Bolin, 2003).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We showed previously that overexpression of IL-6 in transgenic mice leads to a severe reactive gliosis (Brunello et al, 2000), and others demonstrated that the absence of IL-6 impairs reactive astroglial transformation (Klein et al, 1997). However, this effect appears to be dependent on the type of lesion, as MPTP-induced astrogliosis is not impaired in mice lacking IL-6 (Cardenas and Bolin, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…IL-6 is mitogenic for astrocytes (Selmaj et al, 1990), and, together with its soluble receptor (sIL-6Ra), induces a massive reactive gliosis in IL-6/sIL-6Ra double-transgenic mice (Brunello et al, 2000). CNS-specific expression of IL-6 causes lifelong gliosis in transgenic mice (Campbell et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The action of IL-6 in type 1 diabetes pathogenesis may in principle be exerted at the level of the target ␤-cell, and/or at immune regulation, and/or at the hypothalamic-pituitary-adrenal axis. Several investigations of the putative impact of IL-6 on type 1 diabetes have been reported (8,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) (Table 3). …”
Section: The Impact Of Il-6 On Islet Inflammation and β-Cell Apoptosismentioning
confidence: 99%
“…IL-6 not only promotes the survival of certain neuronal cell populations 13 but also the reactive transformation of astrocytes. 14,15 The complex of IL-6 and its primary receptor, IL-6 receptor a (gp80), binds to the transmembrane signal transducer gp130 and activates gp130-associated janus kinases (JAKs) leading to the recruitment and phosphorylation of the signal transducer and activator of transcription 3 (STAT3). Active STAT3 dimerizes, translocates to the nucleus and binds to enhancer elements of target genes, thereby inducing transcriptional activation.…”
mentioning
confidence: 99%